Percepções e ações dos enfermeiros em relação ao racismo institucional na saúde pública - Rosa, Luiz Gustavo Fernandes da (2019)
To know the perceptions and actions of nurses in relation to institutional racism in public health. Method: qualitative, descriptive and exploratory research, with a sample of nine nurses from a city on the north coast of Rio Grande do Sul. Data were collected through semi-structured interviews, analyzed according to the Content Analysis Method. Results: three categories emerged: knowledge about the health of the black population, actions and prevention against institutional racism; Experience in situations of racism, existence of discrimination and inequality in access to health services; Knowledge and opinion on the National Policy of Comprehensive Health of the Black Population and Institutional Racism. Final considerations: nurses perceive institutional racism in a distorted way, with reduced knowledge and provision of actions directed to the health of the black population. However, they emphasize educational means for the prevention and deconstruction of institutional racism in public health.